Adsorption of procion red and congo red dyes using microalgae Spirulina sp - Risfidian Mohadi; Zazili Hanafiah; Hermansyah Hermansyah; Hilda Zulkifli (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2017)
Adsorption of procion red and congo red dyes using microalgae Spirulina sp was conducted. Spirulina sp was obtained by cultivation and production in laboratory scale. Spirulina sp was used as adsorbent for adsorption of dyes. Adsorption process was studied by kinetic and thermodynamic in order to know the adsorption phenomena. The results showed that kinetically congo red is reactive than procion red on Spirulina sp. On the other hand, thermodynamically procion red was stable than congo red on Spirulina sp which was indicated by adsorption capacity, enthalpy, and entropy.